Regulatory macrophages in solid organ xenotransplantation - Thi Xoan Hoang; Jae Young Kim (Korean Journal of Transplantation, 2023)
Due to a critical organ shortage, pig organs are being explored for use in transplantation. Differences between species, particularly in cell surface glycans, can trigger elevated immune responses in xenotransplantation. To mitigate the risk of hyperacute rejection, genetically modified pigs have been developed that lack certain glycans and express human complement inhibitors. Nevertheless, organs from these pigs may still provoke stronger inflammatory and innate immune reactions than allotransplants. Dysregulation of coagulation and persistent inflammation remain obstacles in the transplantation of pig organs into primates. Regulatory macrophages (Mregs), known for their anti-inflammatory properties, could offer a potential solution. Mregs secrete interleukin 10 and transforming growth factor beta, thereby suppressing immune responses and promoting the development of regulatory T cells. These Mregs are typically induced via the stimulation of monocytes or macrophages with macrophage colony-stimulating factor and interferon gamma, and they conspicuously express the stable marker dehydrogenase/reductase 9. Consequently, understanding the precise mechanisms governing Mreg generation, stability, and immunomodulation could pave the way for the therapeutic use of Mregs generated in vitro. This approach has the potential to reduce the required dosages and durations of anti-inflammatory and immunosuppressive medications in preclinical and clinical settings.